Plankton dynamics in the saline lakes of the Vestfold Hills, Eastern Antarctica - Bell, Elanor Margaret (1999)
The paradigm of aquatic food webs has undergone fundamental revision over the past twenty years. Research suggests that a significant proportion of organic material and energy in aquatic ecosystems flows through a "microbial loop" before passage into the classic aquatic food web. Unique Antarctic conditions mean such "bottom-up" control can be of extreme importance during the austral winter. In order to investigate this, the microbial communities and physico-chemical properties of three saline lakes in the Vestfold Hills, eastern Antarctica, Ace, Highway and Rookery, were investigated between December 1995 and February 1997 . The lakes of the Vestfold Hills were formed approximately 8000 years ago following a period of post-glacial marine transgression, which isolated seawater in glacially scoured basins. Post-formation, the chemistry and biology of this isolated seawater underwent significant changes creating a suite of lakes and ponds with highly varied chemical and biological compositions. This study was concerned with meromictic Ace Lake in particular. Physico-chemical results demonstrated that the lake was highly stratified. An upper, nutrient-poor mixolimnion was separated by a thermoclinelhalocline from a lower, nutrient-replete monimolimnion. The monimolimnion was further stratified in terms of oxygen; an oxycline separated an oxic upper stratum from an anoxic lower stratum. At the oxycline, organic substrate sedimenting from above and inorganic nutrients diffusing from below were entrained. This stable stratification exerted a profound influence on the microbial dynamics of Ace Lake. Over the course of its evolution the microbial food web of Ace Lake was truncated and a simple, low diversity community of bacteria, algae and Protozoa, with a paucity of metazoan zooplankton, now dominates. This evolutionary process was illustrated by the intermediate diversity of the protozoan community in recently formed, Rookery Lake. The most dominant micro-organisms in Ace Lake were those which were highly motile and employed versatile nutritional strategies, such as mixotrophy, to remain physiologically active during the austral winter. Ace Lake is an oligotrophic system which receives negligible allochthonous inputs of organic carbon and inorganic nutrients. However, a simple model of the carbon flux within Ace Lake highlighted the fact that autotrophic production within the plankton was insufficient alone to maintain the level of heterotrophic activity observed. Instead, the microbial plankton were dependent on regenerative fluxes of inorganic nutrients and slow-turnover autochthonous carbon, consistent with the concept of the microbial loop.